1990
DOI: 10.1111/j.1348-0421.1990.tb01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Pathogenesis of Salmonella enteritidis in Mice

Abstract: Adherence of many pathogenic organisms to the host cells has been associated with the presence of fimbriae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…These include some of the more virulent and troublesome microorganisms that afflict the human host, such as Vibrio cholerae (4), Salmonella spp. (3,9), Bordetella pertussis (6), and Escherichia coli (10). It is thus reasonable to expect that the hemagglutinins of P. gingivalis are also involved in virulence.…”
mentioning
confidence: 99%
“…These include some of the more virulent and troublesome microorganisms that afflict the human host, such as Vibrio cholerae (4), Salmonella spp. (3,9), Bordetella pertussis (6), and Escherichia coli (10). It is thus reasonable to expect that the hemagglutinins of P. gingivalis are also involved in virulence.…”
mentioning
confidence: 99%
“…However, the bacterial adherence and subsequent invasion are believed to be important steps in the process of Salmonella infection (9,18). Although the type 1 pili of some of the Salmonella serovars are known to be highly adhesive to HeLa and HEp-2 cells (1,5,19), there are only a few reports on the role of pili in invasion of S. typhimurium to cultured cells (9). Ernst et al (6) reported that type 1 pili of S. typhimurium contribute to the bacterial invasion to HEp-2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hemagglutinins specific for human erythrocytes have also been described previously in Escherichia coli (32,34). In addition, Salmonella strains able to agglutinate erythrocytes from a range of animals, or which show only weak hemagglutination of human erythrocytes have been reported (2,3).…”
Section: Resultsmentioning
confidence: 99%